Ameliorative role of diallyl disulfide against glycerol-induced nephrotoxicity in rats - Ashwani Kumar Sharma; Anmoldeep Kaur; Japneet Kaur; Gurpreet Kaur; Apporva Chawla; Mannan Khanna; Harmanpreet Kaur; Harnoor Kaur; Tajpreet Kaur; Amrit Pal Singh (Wolters Kluwer Medknow Publications, 2021)
Introduction: This study investigated the role of diallyl disulfide (DADS) against glycerol-induced nephrotoxicity in rats. Moreover, the role of peroxisome proliferator activated receptor-γ (PPAR-γ) in DADS-mediated renoprotection has been explored. Materials and Methods: Male Wistar albino rats were challenged with glycerol (50% w/v, 8 mL/kg intramuscular) to induce nephrotoxicity. Kidney injury was quantified by measuring serum creatinine, creatinine clearance, urea, potassium, fractional excretion of sodium, and microproteinuria in rats. Renal oxidative stress was measured in terms of thiobarbituric acid reactive substances, superoxide anion generation, and reduced glutathione levels. Hematoxylin-eosin (H&E) and periodic acid Schiff staining of renal samples was done to show histological changes. Glycerol-induced muscle damage was quantified by assaying creatine kinase (CK) levels in rat serum. Results: Administration of glycerol resulted in muscle damage as reflected by significant rise in CK levels in rats. Glycerol intoxication led kidney damage was reflected by significant change in renal biochemical parameters, renal oxidative stress and histological changes in rat kidneys. Administration of DADS attenuated glycerol-induced renal damage. Notably, pretreatment with bisphenol A diglycidyl ether, a PPAR-γ antagonist, abolished DADS renoprotection in rats. Conclusion: We conclude that DADS affords protection against glycerol-induced renal damage in rats. Moreover, PPAR-γ plays a key role in DADS-mediated renoprotective effect.